Slowly vibrating axially symmetric bodies-transverse flow - Srivastava, Deepak (Zielona Góra: Uniwersytet Zielonogórski)
Stokes drag on axially symmetric bodies vibrating slowly along the axis of symmetry placed under a uniform transverse flow of the Newtonian fluid is calculated. The axially symmetric bodies of revolution are considered with the condition of continuously turning tangent.
Keywords: Stokes drag; axially symmetric bodies; Newtonian fluid; axial flow